STRATEGI GURU DALAM PENERAPAN PEMBELAJARAN KONTEKSTUL ABAD 21 DI MA DDI TAKKALASI - Nur Rifiatul Azisah; Muhammad Syukur (Universitas Negeri Makassar, 2020)
This study aims to describe the 21st Century Contextual Learning Application Strategy at MA DDI Takkalasi. This type of research is qualitative with a descriptive approach. The number of informants as many as 11 people who were selected by purposive sampling technique. Data collection techniques using observation, interview, and documentation methods. Checking the validity of the data using the member check technique. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results show that: The results of this study indicate that (1) The application of 21st century contextual learning at MA DDI Takkalasi Barru Regency has been seen in the indicators of implementing the seven components that underlie the implementation of contextual learning, namely constructivism, inquiry, questioning, the learning community, modeling, reflection, and authentic assessment.The factor that hinders the teacher in the contextual learning process is that it comes from the students themselves and the inadequate facilities and infrastructure at school which results in the learning process being constrained.